Adsorption Kinetics for the Removal of Fluoride from Aqueous Solution by Activated Carbon Adsorbents Derived from the Peels of Selected Citrus Fruits - C. Chakrapani; Ch. Suresh Babu; K. N. K. Vani; K. Somasekhara Rao (E-Journal of Chemistry)
Activated carbons (ACs) were prepared from the peels of Citrus documana, Citrus medica and Citrus aurantifolia fruits. Adsorption of fluoride onto these activated carbons was investigated. Effect of contact time in the removal of fluoride from aqueous solution at neutral pH was studied. Five kinetic models; the pseudo first- and second-order equations, intraparticle diffusion, pore diffusion and the Elovich equation, were selected to follow adsorption process. Adsorption of fluoride onto adsorbents could be described by pseudo second-order equation. Kinetic parameters; rate constants, equilibrium adsorption capacities and correlation coefficients, for each kinetic equation were calculated and discussed. The good fitting of kinetic data to pore diffusion and Elovich equations indicate that pore diffusion plays a vital role in controlling the rate of the reaction.